An Analysis of Modality used by The Second-Year Students of Methodist 7 Medan in Speaking - Pasaribu, Yessy Octaviana; Sitorus, Nurhayati; Sitorus, Rosmida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Modality is an important aspect in the functional grammar system, which is used to express the speaker's attitude towards what he say. In the haliday approach, modality describes various degrees of certainty, desire, permission, or need that the speaker shows in a sentence. researchers focus on analyzing student speech. In this study, the researcher used descriptive and qualitative research methods. Based on the results of the analysis applied, researcher found 44 data points from both types, namely Modalization and Modulation. Modalization has a percentage of 25%, while Modulation data has a percentage of 19%. From the research results, the most dominant thing students say when speaking is the type of modalization. the researcher can understand the extent to which students master the use of modality in speaking English, as well as how they choose modal verbs to adjust tone and meaning in various communication situations. It can also provide insight into areas where students may need more training